Oo, wat dom! - Van Os, Erik, 1963-; Van Lieshout, Elle, 1963-; Van Look, Hugo, 1960- (Wommelgem : Van In, 2014)
Mat is boos op Jet. Jet is boos op Mat. Komt het nog goed? (AVI-Start). Vanaf ca. 6 jaar.
Keywords: Ruzies; Boos zijn